The effect of prebiotic supplementation on serum levels of tryptophan and kynurenine in obese women with major depressive disorder: a double-blinded placebo-controlled randomized clinical trial - Fatemeh Khademi; Helda Tutunchi; Elnaz Vaghef-Mehrabani; Mehrangiz Ebrahimi-Mameghani (BMC Research Notes)
Abstract Objective The objective of the present study was to examine the effect of calorie restricted diet (CRD) plus inulin supplementation on serum levels of tryptophan (Trp), kynurenine (Kyn) and Trp/Kyn ratio in obese women with major depressive disorder (MDD). Results In this double-blind placebo-controlled randomized clinical trial, 51 obese women (BMI = 30–40 kg/m2) with mild MDD were assessed for depression level using Hamilton depression rating scale (HDRS). The patients were randomly allocated into either “Prebiotic group” (received 10 g/day inulin) or “Placebo group” (received 10 g/day maltodextrin). All participants also received individualized CRD. Fasting serum levels of Trp, Kyn, and Trp/Kyn ratio were assessed at baseline and after 8 weeks. Results showed slightly greater increases in serum levels of Trp and Trp/Kyn ratio as well as reductions in serum level of Kyn and HDRS score in prebiotic group than placebo group. However, between group differences in these parameters as well as HDRS score were not statistically significant after adjusting for baseline variables at the end of the trial. Results indicates that CRD accompanied by inulin supplementation (10 g/day) did not influence serum levels of Trp, Kyn and Trp/Kyn ratio as well as HDRS score after 8 weeks. Trial registration: The trial was registered in the Iranian registry of clinical trials at 2018-08-02 ( https://www.irct.ir/ ; registration number: IRCT20100209003320N15).